Development of high-stable contact systems to gallium nitride microwave diodes - Belyaev, A.E.; Boltovets, N.S.; Ivanov, V.N.; Kapitanchuk, L.M.; Kladko, V.P.; Konakova, R.V.; Kudryk, Ya.Ya.; Kuchuk, A.V.; Lytvyn, O.S.; Milenin, V.V.; Sheremet, V.N.; Sveshnikov, Yu.N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
High-stable heat-resistant low-resistance contact systems with diffusion barriers involving quasi-amorphous TiBx layers are suggested and studied. We have performed the structural and morphological investigations along with studies of Auger concentration depth profiles in the contacts both before and after rapid thermal annealing. It is found that the Au−TiBx−Al−Ti−GaN contact layers with diffusion barriers retain both a layered structure of the contact metallization and the value of contact resistivity practically unchanged up to the temperature Т ≈ 700 ºС. At the same time, the layered structure of the metallization in standard Au−Ti−Al−Ti−GaN contact systems breaks down at such rapid thermal annealing. It is shown that the contact metallization of both types demonstrates the tunnel current flow mechanism in the temperature range 225−335 K, whereas the current flow mechanism is thermionic in the range 335−380 K, the Schottky barrier height being ~0.16 eV. For the best samples under consideration, the contact resistivity was no more than 10⁻⁶ Ohm∙cm² .